Experience the serenity of PG2 Tanjung Jaga De Camphece, Yan: beach camping getaway / Farhan Faat… [et al.] - Faat, Farhan; Hashim, Norliana; Sulaiman, Suria; Nordin, Nakia (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
Welcome to Yan, Kedah's Tanjung jaga De Camphece, a hidden spot where the harmony of the sea meets the tranquillity of an ethereal landscape. Picture yourself in a mystical coastal retreat, where the simplicity of beach camping and the soothing sound of the waves create an unforgettable escape. The breathtaking vista at Tanjung Jaga De Camphece awaits you as you arrive. As the sun starts to rise, it casts a golden glow that illuminates the tranquil waters and flawless beach.